2007
DOI: 10.1111/j.1558-5646.2007.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Resistance in the Drosophila?macrocheles System: A Negative Genetic Correlation Between Ectoparasite Resistance and Reproduction

Abstract: Genetic variation for parasite resistance occurs in most host populations. Costs of resistance, manifested as reduced fitness of resistant genotypes in the absence of parasitism, can be an important factor contributing to the maintenance of this variation. One powerful tool for detecting costs of resistance is the study of correlated responses to artificial selection. Provided that experimental lines are recently derived from large outbreeding populations, and that inbreeding is minimized during the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 74 publications
5
56
0
Order By: Relevance
“…Factors that might potentially predispose inbred individuals to disease include differences in behavioural resistance (Calleri et al 2006;Luong & Polak 2007) or immune response (Reid et al 2007), which might be owing, in part, to differences in condition or nutrition (Moller et al 1998;Blanco et al 2001;Koski & Scott 2001) among individuals with different inbreeding coefficients. Previous field studies have explored links between inbreeding and components of the immune response (Reid et al 2007), inbreeding and disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that might potentially predispose inbred individuals to disease include differences in behavioural resistance (Calleri et al 2006;Luong & Polak 2007) or immune response (Reid et al 2007), which might be owing, in part, to differences in condition or nutrition (Moller et al 1998;Blanco et al 2001;Koski & Scott 2001) among individuals with different inbreeding coefficients. Previous field studies have explored links between inbreeding and components of the immune response (Reid et al 2007), inbreeding and disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that resistance-selected lines experience a significant reduction in female fecundity, and that this effect is temperature-dependent (Luong and Polak, 2007). In the present study, we test for genetic trade-offs between ectoparasite resistance and larval competitive ability in lines of Drosophila nigrospiracula selected for resistance against an ectoparasitic mite.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, heritable genetic variation for this behavioral form of resistance has been documented in natural populations. Heritability for resistance was previously estimated to be 0.12-0.15 (Polak, 2003;Luong and Polak, 2007), demonstrating that additive genetic variation for ectoparasite resistance exists in natural populations.…”
Section: Study Systemmentioning
confidence: 99%
See 2 more Smart Citations